A composition for treating leukemia - Abdullah, Rasedee; Rahman, Heshu Sulaiman; Abdul, Ahmad Bustamam; How, Chee Wun; Yeap, Swee Keong (2013)
The present invention relates to a composition for treating leukemia. The composition comprises of effective amount of zerumbone and a pharmaceutically acceptable carrier characterized in that the carrier is a nanostructure lipid carrier. The composition is safe for administration in human body and shows enhanced bioavailability. The present invention also relates to a method for preparing the composition.